The Firaq Ḥadīth amongst the Shī‘īs1 and Their Treatment of It - Mohammad Nasrin Nasir (Refleksi: Jurnal Kajian Agama dan Filsafat, 2012)
This article describes the value of the firaq ḥadīth according tothe views of the Shī‘ī authors who had included this ḥadīth in their books.The method of enquiry would be first to determine whether this same firaq ḥadīth exist in the major collections of the Shī‘a and its variants; to locate and translate them, and to find out the views of Shī‘ī scholars regarding them.DOI: 10.15408/ref.v13i3.906